School as a Learning Organization. School Climate in Digital Society - Mariana Georgiana Moraru (National Centre for Policy and Evaluation in Education, 2019)
The paper analyses the components of the educational climate in the school organization. The latter facilitates and co-participates in the learning processes while constantly developing itself. The importance of the educational climate in defining a school is metaphorically underlined by Freiberh and Stein (1999), which described the school climate as "the heart and soul of the school, and the essence that directs teachers and pupils to love school and to want to be part of it." In recent years, worrying studies have emerged about the feelings that both students and teachers associate with the school. According to a report on the state of education in Romania, published by UNICEF in 2013, our country is the last in Europe in terms of the well-being of young people. Even when it comes to teachers, the educational reality is not very different. A recent study (2018) by the Romanian Business Leaders Foundation (RBL) and D & D Research shows that Romania occupies the antepenultimate place in the world and the last place in Europe in global index of the status of teachers in society. In order to build a learning climate and to support the development of schools, it is first necessary to carefully analyse the many dimensions of the educational climate in order to understand the complexity and value of this concept.